Close range hyperspectral imaging of plants: A review. (December 2017) - Mishra, Puneet; Asaari, Mohd Shahrimie Mohd; Herrero-Langreo, Ana; Lohumi, Santosh; Diezma, Belén; Scheunders, Paul
Abstract : The increasing need to develop a rapid understanding of plant functional dynamics has led to the employment of sensor technology for non-destructive assessment of plants. Hyperspectral Imaging (HSI) being an integration of two modalities, imaging and point spectroscopy, is nowadays emerging as a potential tool for rapid, non-destructive and automated close range assessment of plants functional dynamics both in terms of structure and physiology. Firstly, this paper presents an overview of some basic concepts of close range HSI on plants, concerning the plant–light interaction, instrumental setup, and spectral data analysis. Furthermore, the work reviews recent advances of HSI for plant related studies under controlled experimental conditions as well as in natural agricultural settings. Applications are discussed on foliar content estimation, variety identification, growth monitoring, stress and disease-related studies, phenotyping and adoption of HSI in high-throughput phenotyping platforms (HTPPs). Close range HSI is a challenging task and suffers from technical complexities related to external factors (e.g. illumination effects) as well as plant-related factors (e.g. complex plant geometry). The paper finally discusses some of the technical challenges related to the implementation of HSI in the close range assessment of plant traits. Highlights: HSI is an automated, non-destructive and rapid alternative to explore plant traits. It acquires both chemical and structural information related with plant traits. Phenotyping, disease, species identification, foliar chemistry estimation. Illumination effects are the major technical challenge to be dealt with.